Antimicrobial activity of Azadirachta Indica (neem) leaf, bark and seed extracts - Raja Ratna Reddy, Y.; Krishna Kumari, C.; Lokanatha, O.; Mamatha, S.; Damodar Reddy, C. (Research gate, 2020)
Screening of medicinal plants for bioactive compounds leads to development of less expensive new antimicrobial agents with improved safety and efficacy. Azadirachta Indica (neem) is a multipurpose tree with multiple health benefits. Different parts of the plant are shown to exhibit antimicrobial effects against a wide variety of microorganisms. In the present study we compared the antimicrobial efficacy of aqueous extracts of leaf, bark and seeds of A. Indica against human pathogenic bacteria (Staphylococcus aureus, Enterococcus feacalis, Proteus mirabilis and Pseudomonas aeuroginosa) and fungi (Aspergillus fumigatus and Candida albicans). Agar well diffusion method and micro-broth dilution methods were used to determine the minimum inhibitory concentration (MIC). Results showed that leaf extract exhibited strong antimicrobial activity against bacteria and fungi at all the concentrations tested (500, 1000 and 2000µg/ml). Antimicrobial activity of bark extract was found to be moderate on bacteria and fungi (effective at 1000 and 2000µg/ml), whereas seed extract exhibited least antimicrobial activity. Minimum inhibitory concentration (MIC) of leaf and bark extract was found to be in the range of 500 to 2000µg/ml for all the tested microorganisms, where as the seed extract did not inhibit the microorganisms at all the concentrations tested except Candida albicans (1000µg /ml). Our results suggest that aqueous extracts of Azadirachta Indica leaf and bark exhibit high antimicrobial activity.
Keywords: Azadirachta Indica; Agar well diffusion method; Antimicrobial; MIC; Pathogenic microorganisms